Virtual communication is commonly used in Finnish interstitial lung disease multidisciplinary meetings - Salonen Johanna; Nurmi Hanna; Hodgson Ulla; Hasala Hannele; Kilpeläinen Maritta; Hollmen Maria; Purokivi Minna; Kaarteenaho Riitta (TAYLOR & FRANCIS LTD, 2025)
Multidisciplinary meeting (MDM) is a core element in the diagnosis of interstitial lung diseases (ILD). The aim of the study was to investigate the implementation and key elements related to ILD MDMs in Finnish specialized care, which is characterized by long travel distances and a large number of small centers treating patients suffering from ILDs. An electronic questionnaire was sent to ILD experts working at five academic centers of Finland regarding the implementation of ILD MDMs with the focus on utilization of virtual communication. Responses were received from all academic centers of Finland (n = 5) whose catchment areas cover all of Finland. ILD MDMs were organized in each center approximately every two weeks and the core participants included a radiologist, respiratory physicians, junior staff, pathologist and a rheumatologist. All non-academic centers could refer their patients to be evaluated in ILD MDM of an academic center. Virtual communication was utilized by all academic centers in the implementation of ILD MDMs, being most common among small centers located in Eastern and Northern Finland. Virtual access to ILD MDM of an academic center was available in most parts of Finland, enabling small centers to benefit from the ILD expertise of academic centers.